Implementasi Pendidikan Karakter di Kampung Naga dalam Konsep SiIih Asah, Silih Asih, Silih Asuh - Dirga Candra Styawan; Danella Fiorenza Zhafiri; Fleta Margaretha Kusuma Wardani; Gandhi Adidaya; Raharjo (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the characteristics and implementation of character education in Kampung Naga, Neglasari Village, Salawu District, Tasikmalaya Regency, West Java Province. Character education in Kampung Naga is an effort made by parents and village elders to inherit the customs and habits that they have maintained for generations. The method used in this research is descriptive qualitative, by collecting data through observation, interviews, and literature studies. The results showed that there is a unique method of character education in Kampung Naga, namely through diniyah school. In its implementation, character education in Kampung Naga has proven successful in forming a generation that is able to adapt to the times but does not forget its identity as part of the indigenous community. In addition, character education in Kampung Naga Indigenous Community is expected to be able to implement the concept of silih asah, silih asih, and silih asuh. Through this research, it is hoped that it can contribute scientifically and provide a deeper understanding of the importance of character building in maintaining customs and culture, especially in Kampung Naga.